The use of social media in mitigating social issues in Malaysia / Ali Fauzi Ahmad Khan - Ali Fauzi , Ahmad Khan (2022)
This research considers how social media may have fostered innovative technology use to mitigate societal issues. The article presents 3 cases. First, it shows how social media can help and hinder crime prevention efforts. Second, it examines social media use during a disaster. Third, it explains how social media can be used for social advocacy using the response to a ban on homeless people from city streets. Most social media research focuses on user behavior, organizational applications, and data mining. This research emphasizes users' perspectives. It uses structured pragmatic-situational (SPS) data collection and analysis to conduct case studies. The three cases involved sixty-six interviews totaling 100 hours. Follow-up interviews and document analysis revealed more user concerns and functions.The research findings were analyzed using the affordances and constraints theory in case one, the resource-based view theory in case two, and the "grassroots" or community organizing theory in case three. Each chapter presents findings based on relevant theories. For example, case one presents the affordances and constraints of social media in crime prevention. Case two suggests a process diagram of how social media was used during the disaster. Case three, using theory, describes how power appears to be shifting from authorities to society.It will contribute to social media research by developing a theory that explains how society uses social media to solve problems. Events with high social media usage will be analyzed using interviews and social media sites. The emergent theory will advance social media research. In addition, unknown issues will be introduced, contributing to social media research.